ANALISIS PERBANDINGAN KINERJA KEUANGAN SEBELUM DAN SESUDAH AKUISISI PADA PT PHAPROS TBK - Muhammad Bagus Alfirdaus; Sri Murwanti (LP2M Universitas Bina Bangsa, 2024)
This study examines the comparative analysis of financial performance before and after the acquisition of Pt Phapros Tbk. This research method is quantitative. The population of this study is in the form of time series data or consecutive data from the annual financial statements of PT Phapros Tbk for the 8-year period (2015-2022) available on the official website of PT Phapros Tbk https://www.phapros.co.id/. All samples are based on time series data for a period of 4 years before acquisition (2015-2018) and 4 years after acquisition (2019-2022). The data used is secondary data. The data collection method in this study used documentation methods. This analysis technique is carried out with parametric difference tests or non-parametric difference tests and normality tests. The data in this study will be processed using SPSS software. The result of this study is the Current Ratio (CR) shows that there is a difference before and after the acquisition at PT Phapros Tbk. This can be seen from the results of the Wilcoxon sign rank test which shows a significant value of 0.144 < 0.05. Based on the results of the Wilcoxon sign rank test which showed a significant value of 0.068 > 0.05. The results show that there is a difference in Return on Asset (ROA) ratio before and after the acquisition at PT Phapros Tbk. There is a difference in Debt to Equity Ratio (DER) before and after the acquisition at PT Phapros Tbk. This is based on the results of the Wilcoxon sign rank test showing a significant value of 0.144 > 0.05. The results of this study Net Profit Margin (NPM) show that there is a difference before and after the acquisition at PT Phapros Tbk. This can be seen from the results of the Wilcoxon sign rank test which shows a significant value of 0.715 > 0.05. Based on the results of the Wilcoxon sign rank test which showed a significant value of 0.068 > 0.05. The results show that there is a difference in the Total Asset Turn Over (TATO) ratio before and after the acquisition at PT Phapros Tbk.